Detecting Student Misconceptions about Physics Using Three Tier Diagnostic Test with Analysis Certainty of Response Index - Makhrus, Muh.; Hidayatullah, Zul (UNIVERISTAS PGRI MADIUN, 2021)
Misconceptions are an obstacle in the learning process, especially in physics. One way to detect misconceptions is to use a three-tier diagnostic test and analyze it using the Certainty of Response Index (CRI). The purpose of this study was to detect students' misconceptions on straight motion material using a three-tier diagnostic test with CRI analysis. This type of research is descriptive research. The sample in this study was taken from students at three high schools in East Lombok district, NTB. The number of samples in this study was 132 students. This test instrument consists of 10 question items. The results showed that students still experienced many misconceptions in straight motion material.